A study on the behavior of beam-column connections in precast concrete structures: experimental analysis - Kataoka,M. N. (2012)
Due to the large increase in the use of precast concrete structures in multistory buildings, this work covers a study on the behavior of beam-column connection with emphasis on the continuity provided by the slab reinforcement. Two prototypes were tested, each one with a different detail of the continuity reinforcement distribution. In both connections, the steel area used on the concrete cover of the hollow core slab was the same, varying the amount of bars that passed through the column and the ones that were placed adjacent to the column. The experimental results showed that the connection with bars adjacent to the column presented stiffness increase and a better cracking control. According to the classification the two tested connections can be considered semi-rigid.